A Review of FDA-Approved Antiparasitic Drugs in USA for Sheep and Goats: Their Synthesis and Pharmaceutical Use - Davide Benedetto Tiz; Črtomir Podlipnik (Shiraz University of Medical Sciences, 2023)
This review describes the Food and Drug Administration (FDA)-approved antiparasitic drugs for sheep and goats in the USA updated to 2021. The emerging drug resistance is posing a significant burden for the treatment of parasitic infections in these small ruminants and the need for novel antiparasitic drugs is urgent. Sheep and goats are producing every year important resources such as milk and wool, among others. This work incorporates the OneHealth approach which focuses not only on human health, but also on animal health and the environment in an interdependent modus operandi. The dynamic equilibrium among these three sectors plays a fundamental role in general healthcare. Drug discovery (e.g., a novel benzimidazole recently identified) and drug delivery (incorporation of the antiparasitic agent into the proper carrier to increase effectiveness) have provided some promising results in recent time. This should go hand-in-hand with the scientific awareness. Education is key in spreading the word about the responsible use of antiparasitic drugs. The synthesis of the currently approved drugs will be provided including synthetic procedures which date from 1961 to 2021. More synthetic pathways, when available, will be described. Their mechanism of action and ecotoxicological data will be presented as well.